Vertical Profile of Banda Sea Temperature Related to El Niño Events in the East Pacific and Central Pacific - Prasetyo, Budi; Pusparini, Nikita; Radjawane, Ivonne Milichristi (Indonesian Institute of Sciences, 2019)
Eastern Pacific (EP) and Central Pacific El Niño have different characteristics such as mechanism, evolution, impact to Sea Surface Temperature (SST), and rainfall. The character of two types of El Nino affect the temperature of the sea, on the near-surface as well as in deeper layer, in other regions including Banda Sea. This study is aimed to understand the response of Banda Sea vertical sea temperature profile to both El Niño types using sea temperature data from Simple Ocean Data Assimilation (SODA) v.2.2.4 from January 1950 until December 2010 (60 years), Oceanic Nino Index (ONI), and mixed layer depth (MLD) from SODA3. Eastern Pacific El Niño and CP El Niño cooled Banda Sea about -1.5°C and 0.9°C, respectively. The maximum cooling due to both El Niño occurred in the thermocline layer (at the depth of 90 to 120m). The maximum temperature decrease during EP El Niño occurred at the depth of 90 to 120 m, while during CP El Niño the maximum temperature decrease was at 140 to 160 m and 160 to 200m in western and eastern Banda Sea, respectively. The temperature of the near-surface layer responded rapidly to CP El Niño while in the deep layer the temperature responded more to EP El Niño. The Banda deep sea layer was cooling after both types of El Niño extinct while the temperature of near-surface layer was increasing when CP El Niño extinct